Sesquiterpenos produzidos pelo fungo endofítico Phomopsis cassiae com atividade antifúngica e inibidora de acetilcolinesterase - Zanardi, Lisinéia M. [UNESP] (2012)
SESQUITERPENES PRODUCED BY ENDOPHYTIC FUNGUS Phomopsis cassiae WITH ANTIFUNGAL and ACETYLCHOLINESTERASE INHIBITION ACTIVITIES. Two new diastereoisomeric cadinanes sesquiterpenes 3,9-dihydroxycalamenene (1-2), along with the known 3-hydroxycalamen-8-one (3) and aristelegone-A (4), were isolated from ethyl acetate extract of Phomopsis cassiae, an endophytic fungus in Cassia spectabilis. Their structures, including relative stereochemistry, were determined on the basis of detailed interpretation of 2D NMR spectra and comparison with related known compounds. Compounds 1-4 displayed antifungal activity against the phytopathogenic fungi Cladosporium cladosporioides and C. sphaerospermum, as well as inhibition of acetylcholinesterase.